(untitled) (OODBODHAN, 2026)
The recently upgraded four-lane Prithvi Highway in Nepal requires performance-based evaluation to assure sustained operational efficiency under rapidly increasing traffic demand. This study analyzes the traffic performance of two representative highway segments, Kamalbari and Gunadi, using the Indian Highway Capacity Manual (Indo-HCM) framework. Videographic traffic surveys had been conducted for three successive days to obtain classified traffic volumes and individual vehicle speeds under heterogeneous traffic conditions. Major traffic performance parameters such as space mean speed, operating speed, capacity, traffic density, and level of service were evaluated. The analysis revealed that two-wheelers dominated the traffic stream at both locations, contributing nearly 45% of total traffic, followed by standard cars at approximately 15%. After adjusting for shoulder width, the estimated capacities were 3,787 PCU/h/dir on the Kamalbari segment and 3,677 PCU/h/dir on the Gunadi segment. Kamalbari performed under LOS A, representing free-flow conditions, while Gunadi maintained LOS B, indicating stable flow with slightly greater vehicle interactions. These findings indicate that the upgraded four-lane highway is currently operating efficiently; yet, regular monitoring and timely maintenance will be necessary to accommodate future traffic growth and maintain acceptable service levels.